A model approach for considering nonmetallic inclusions in the calculation of the local tooth root load-carrying capacity of high-strength gears made of high-quality steels. (November 2019) - Fuchs, D; Schurer, S; Tobie, T; Stahl, K
Demands for higher performance have caused a need for improved component characteristics, e.g. through surface strengthening of gears and increased cleanliness of gear steels. Unfortunately, a resultant drawback is that cracks in such high-strength gears are more often initiated in the material matrix at nonmetallic inclusions and not at the surface. In standardized calculation methods, the degree of cleanliness of steels is not yet directly correlated to the tooth root load-carrying capacity. This paper considers the effects of nonmetallic inclusions in the steel matrix on the tooth root strength based on the theoretical approach of Murakami.